Personal Branding Digital Natives di Era Komunikasi Media Baru (Analisis Personal Branding di Media Sosial Instagram) - Oryza Devi Salam (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
The nature of humans in their lives is to carry out communication activities. An individual can be said to communicate with other people if both have an understanding of the meaning of the message conveyed in their interactions. The progress of information communication technology provides an opportunity for individuals to interact more easily through the internet. In 2017, the number of internet users in Indonesia was recorded at 143.26 million, or 54.68 percent of Indonesia's total population. This number increased compared to the previous year, namely in 2016 which was recorded at 132.7 million. Of the numbers recorded, 130 million of them are active on social media in term of New Media Communication, or noted as information technology-based communication, makes social media as primary chosen for individuals interacting socially in cyberspace. This study aims to analyze how the personal branding forming in social media instagram refer to eight laws of personal branding such as: specialization, leadership, personality, distinctiveness, visibility, unity, persistence and goodwill. The best personal branding must be meets on these eight laws. The type of research conduct as qualitative descriptive, which the method is case study. The data used are primary data from interviews with selected informants and secondary data: documents in the form of photos and texts of digital natives on their Instagram. The data were analyzed by data reduction, data display by arranging it according to the pattern and then verification that is drawing the conclusion to answer the research question. Refer to the results of the study, the conclusion is personal branding of digital natives on Social Media Instagram need to be manage to meet all eight laws of personal branding.Keywords: Communication, Digital Natives, New Media, Social Media